Filsafat Pendidikan Kristiani dalam Pertanian Padi Darat: Kemenjadian Misteri dan Moralitas - Munte, Alfonso (PEADA': Jurnal Pendidikan Kristen, 2024)
The purpose of this study was to explore Christian religious education teachers' views on the synthesis of adat, education, curriculum, and interfaith spiritual values manifested in the land rice planting ritual. This includes aspects such as prayers and gotong royong activities that emphasize togetherness, well-being, and a deep understanding of the philosophy of life. Based on brief surveys through 17 research subjects were mostly students of Palangka Raya and came from East Barito and 2 Christian religious education teachers in one of the high schools in East Barito, the researcher found information that currently, learning activities through land rice planting have diminished and are even threatened with extinction. In fact, land rice planting brings interfaith spirituality through prayer with all kinds of meanings (togetherness, mutual cooperation, and sufficiency). Qualitative research with brief survey and interview techniques to Christian religious education teachers provides space for information on high school education through Christian religious education teachers as research subjects who are experts as well as experienced in synthesizing between adat, education (curriculum, teachers, students and society). The results showed such education is an education that translates prayer as ritual space between religions, customs, philosophy and education through the process of planting land rice (tebas tebang, Mu'au, ritual [prayer/mystical and offerings from the earth]) from the teacher's perspective. Tujuan penelitian ini adalah untuk mengeksplorasi pandangan para guru pendidikan agama Kristen mengenai sintesis antara adat, pendidikan, kurikulum, dan nilai-nilai spiritual lintas agama yang terwujud dalam ritual penanaman padi darat. Hal ini mencakup aspek-aspek seperti doa dan kegiatan gotong royong yang menekankan kebersamaan, kesejahteraan, serta pemahaman mendalam tentang filosofi hidup. Berdasarkan survei singkat melalui 17 subjek penelitian yang sebagian besar merupakan pelajar Palangka Raya dan berasal dari Barito Timur serta 2 guru pendidikan agama Kristen di salah satu SMA di Barito Timur, ditemukan informasi bahwa saat ini kegiatan pembelajaran melalui penanaman padi darat sudah semakin berkurang bahkan terancam punah. Padahal, penanaman padi darat menghadirkan spiritualitas lintas agama melalui doa dengan segala macam maknanya (kebersamaan, gotong royong, dan kecukupan). Penelitian kualitatif dengan teknik survei dan wawancara kepada guru pendidikan agama Kristen memberikan ruang informasi tentang pendidikan sekolah menengah atas melalui guru pendidikan agama Kristen sebagai subjek penelitian yang ahli sekaligus berpengalaman dalam mensintesiskan antara adat, pendidikan, kurikulum, guru, siswa, dan masyarakat. Hasil penelitian menunjukkan pendidikan yang demikian adalah pendidikan yang menerjemahkan doa sebagai ruang ritual antara agama, adat, filosofi dan pendidikan melalui proses tanam padi darat (tebas tebang, Mu'au, ritual [doa/mistik dan persembahan dari bumi]) dari sudut pandang guru.